Percentage of Carcass, Gizzard, Liver and Heart Of Quail That Were Fed Temulawak Seed in Drinking Water - R. Oktovian; Nuraini; Hafid, Harapin (Talenta Publisher, 2022)
That was study aims to determine the effect of temulawak juice in drinking water on slaughter weight and carcass weight. The treatment in this study used quail and ginger extract. The data obtained were then tabulated using analysis of variance and continued with Duncan's multiple distance test. The results of this study indicate that the application of temulawak juice in drinking water did haven’t a significant effect on the percentage of quail carcass, liver and gizzard, but had a significant effect on the percentage of heart.